Comparative performance of ARIMA and GARCH Models in modelling and forecasting volatility of Malaysia market properties and shares - Miswan, Nor Hamizah; Hamzah, Khairum; Ngatiman, Nor Azazi; Zamzamir Zamzamin, Zaminor (HIKARI LTD, 2014)
Market properties and shares are important in the field of finance in order to measure the economic growth of a country. These market properties are volatile time series as they have huge price swings in a shortage or an oversupply period. In this study, we use two time series models which are Box-Jenkins Autoregressive Integrated Moving Average (ARIMA) and Generalized Autoregressive Conditional Heterocedasticity (GARCH) models in modelling and forecasting Malaysia property market. The capabilities of ARIMA and GARCH models in modelling and forecasting Malaysia property market will be evaluated by using Akaike's Information Criterion (AIC), Mean Absolute Percentage Error (MAPE) and Root Mean Squared Error (RMSE). It can be concluded that Box-Jenkins ARIMA model perform better compared than GARCH model in modelling and forecasting Malaysia market properties and shares.